2014
DOI: 10.1002/2014jd021490
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of observed and model‐derived soil moisture‐evaporative fraction relationships over the United States Southern Great Plains

Abstract: The relationship between soil moisture (SM) and evaporative fraction (EF) is an important component of land-atmosphere interactions. Frequently, land-atmosphere studies are based on land-surface models and not on observations. This study examines SM-EF interactions over the United States Southern Great Plains using both in situ observations and simulations from the Variable Infiltration Capacity hydrologic model. Specifically, we evaluate how the relationship between SM and EF varies by season, we determine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 27 publications
(51 reference statements)
3
45
0
Order By: Relevance
“…Similar to Williams and Torn [], we found that increasing LAI tended to produce greater EF at the winter wheat site but that this effect saturated around 2.5 m 2 m −2 (Figure a). Additionally, consistent with Ford et al [], we found that the relationship between θ v and EF at the grassland/pasture site was only strong below ~0.28 m 3 m −3 LAI (e.g., Figure b). However, Ford et al [] also found that the relationship between soil moisture and EF was dependent on net radiation, with the EF‐soil moisture relationship weakening at low radiation levels.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to Williams and Torn [], we found that increasing LAI tended to produce greater EF at the winter wheat site but that this effect saturated around 2.5 m 2 m −2 (Figure a). Additionally, consistent with Ford et al [], we found that the relationship between θ v and EF at the grassland/pasture site was only strong below ~0.28 m 3 m −3 LAI (e.g., Figure b). However, Ford et al [] also found that the relationship between soil moisture and EF was dependent on net radiation, with the EF‐soil moisture relationship weakening at low radiation levels.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, consistent with Ford et al [], we found that the relationship between θ v and EF at the grassland/pasture site was only strong below ~0.28 m 3 m −3 LAI (e.g., Figure b). However, Ford et al [] also found that the relationship between soil moisture and EF was dependent on net radiation, with the EF‐soil moisture relationship weakening at low radiation levels. Net radiation was not found to be an important variable in our analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Concurrently, limited surface radiation (e.g., Figure c) reduces sensible heating, thereby inhibiting the land surface's ability to modify the atmosphere through latent and sensible heat fluxes. These conditions are similar to the “energy‐limited” evaporative regime, in which incoming solar radiation, not soil moisture, determines variations in surface evaporative fraction [ Ford et al ., ]. Examples of morning (06:00 LST) and afternoon (12:00 LST) atmospheric profiles from 22 June 2004 over Lamont, Oklahoma, demonstrate such conditions (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…That is, the sign and magnitude of land–atmosphere interactions are believed to be relatively stable over time. However, the mechanisms through which soil moisture influence air temperature are not static, but vary on diurnal (Gentine et al , ), seasonal (Guo et al , ), inter‐annual (Ford et al , ), and inter‐decadal (Sheffield and Wood, ) timescales. For example, soil moisture heterogeneity across tens‐to‐hundreds of kilometres can modify synoptic conditions on diurnal time scales leading to the generation of mesoscale convective systems (Frye Mote, ; Taylor et al , ).…”
Section: Introductionmentioning
confidence: 99%